Exceptionally preserved beetles in a Triassic coprolite of putative dinosauriform origin - Qvarnström, Martin; Fikáček, Martin; Vikberg Wernström, Joel; Huld, Sigrid; Beutel, Rolf G; Arriaga-Varela, Emmanuel; Ahlberg, Per E; Niedźwiedzki, Grzegorz (Current biology, 2021)
The Triassic was a crucial period for the early evolution and diversification of insects, including Coleoptera1-3-the most diverse order of organisms on Earth. The study of Triassic beetles, however, relies almost exclusively on flattened fossils with limited character preservation. Using synchrotron microtomography, we investigated a fragmentary Upper Triassic coprolite, which contains a rich record of 3D-preserved minute beetle remains of Triamyxa coprolithica gen. et sp. nov. Some specimens are nearly complete, preserving delicate structures of the legs and antennae. Most of them are congruent morphologically, implying that they are conspecific. Phylogenetic analyses suggest that T. coprolithica is a member of Myxophaga, a small suborder of beetles with a sparse fossil record, and that it represents the only member of the extinct family Triamyxidae fam. nov. Our findings highlight that coprolites can contain insect remains, which are almost as well preserved as in amber. They are thus an important source of information for exploring insect evolution before the Cretaceous-Neogene "amber time window." Treated as food residues, insect remains preserved in coprolites also have important implications for the paleoecology of insectivores, in this case, likely the dinosauriform Silesaurus opolensis.
Keywords: Coleoptera; brouci; Amber; Phylogeny; Myxophaga; zkameněliny; Triamyxa; Animals; Fossils; Silesaurus; Triassic; coprolites; paleoecology; zvířata; fylogeneze; synchrotron microtomography; jantar